SISTEM E-COMMERCE BERBASIS WEBSITE DENGAN INTEGRASI AUGMENTED REALITY (AR) PADA BUTIK GPM COLLECTION - Ahmad Deni Setiawan; Muhammad Syahputra Novelan (Smart Education, 2025)
Abstract: The innovation that emerged in today's era is e-commerce, a change in customer behavior that originally shopped conventionally turned into online shopping. With the increase in internet users in Indonesia, it is certainly very good to support businesses engaged in online. One of the businesses engaged in online is the gpm collection in Medan city which sells clothing products. As long as it stands, gpm collection does not have a website and does not maximize in reaching more customers widely. This research aims to create a gpm collection e-commerce website that has augmented reality features to display products in virtual so as to strengthen competitiveness in market. the website was created using the codeigniter4 framework with the programming language php, html, css, javascript, and the database used is mysql. The research method used is the agile method, a method based on an iterative work process with a software development process that is carried out sequentially, starting from the stages of needs, design, development, testing to implementation. The implementation results show that there is an increase in productivity from gpm collection employees, being able to reach more customers, and building a professional business identity.Â Keywords: e-commerce, augmented reality, agile, codeigniter4, gpm collection.Abstrak: Inovasi yang muncul di era saat ini adalah e-commerce, perubahan perilaku customer yang awalnya belanja secara konvensional berubah menjadi belanja online. Dengan meningkatnya pengguna internet diindonesia tentu sangat baik untuk mendukung bisnis yang bergerak dibidang online. Salah satu bisnis yang bergerak dibidang online adalah gpm collection di kota Medan yang menjual produk pakaian. Selama berdiri, gpm collection belum memiliki website dan kurang memaksimalkan dalam menjangkau lebih banyak customer secara luas. Penelitian ini bertujuan untuk membuat website e-commerce gpm collection yang memiliki fitur augmented reality untuk menampilkan produk secara virtual sehingga memperkuat daya saing dipasar. Website dibuat menggunakan framework codeigniter4 dengan bahasa pemrograman php, html, css, javascript, dan database yang digunakan adalah mysql. Metode penelitian yang digunakan adalah metode agile, metode yang didasarkan pada proses pengerjaan berulang dengan proses pengembangan perangkat lunak yang dilakukan secara berurutan, dimulai dari tahap kebutuhan, perancangan, pengembangan, pengujian hingga implementasi. Hasil implementasi menunjukkan bahwa terdapat peningkatan produktifitas dari karyawan gpm collection, mampu menjangkau customer lebih banyak, dan terbangunnya identitas bisnis yang profesional.Â Kata kunci: e-commerce,augmented reality, agile, codeigniter4, gpm collection.